The Effect of Profitability, Leverage, and Firm Size on Firm Value with Dividend Policy as an Intervening Variable - Robert Jao; Paulus Tangke; Anthony Holly; Felisya The; Riza Praditha (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The purpose of this study is to investigate the effect of profitability, leverage, and firm size on firm value mediated by dividend policy. This study employs signal theory and the bird-in-hand theory to explain the relationship between variables. The population used is non-financial companies listed on the Indonesia Stock Exchange (IDX) during the period 2022-2024. The data sources used are secondary data in the form of annual reports obtained from the Indonesia Stock Exchange and the company's official website. The sample consists of 118 companies, selected over three years, using a purposive sampling method. The results of the study indicate that profitability has a significant positive effect on dividend policy, while leverage has a significant adverse effect on dividend policy; however, firm size does not significantly affect dividend policy. The study's findings also revealed that profitability, leverage, firm size, and dividend policy have a significant positive effect on firm value. Finally, this study found that dividend policy mediates the relationship between profitability and leverage on firm value. However, dividend policy is unable to mediate the relationship between firm size and firm value.